Feeding Behavior of Fattening Bulls Fed Six Times per Day Using an Automatic Feeding System - Schneider, Laura; Volkmann, Nina; Kemper, Nicole; Spindler, Birgit (Frontiers in Veterinary Science, 2020)
The usage of automatic feeding systems (AFS) in cattle offers multiple advantages, mostly due to the possibility of an increased feeding frequency. While it is gaining more and more importance in dairy farming, there is still a lack of experience and scientific knowledge regarding its use in fattening cattle. The aim of this study was to describe the behavior of 56 Simmental bulls fed with an AFS six times daily a total mixed ration. The animals arrived at the farm with an average age of 148 ± 11 days. They were housed in four straw-bedded pens in groups of 14 animals each. Their average slaughter age was 558 ± 20 days. Behavioral observations were made during three observation periods (OP) at an average of 11, 14 and 16 months of age. Using scan sampling, feeding and lying behavior of all animals and the order of bulls feeding after feed delivery were recorded. Furthermore, body condition and health status were monitored and complemented with the carcass weights. Body condition, health status and carcass weights of the bulls were found to be satisfactory: Mean body condition score increased from 2.8 ± 0.3 in OP1 to 3.0 ± 0.1 in OP3 and mean carcass weight was 432.71 ± 40.82 kg. No severe health problems occurred. The feeding activity of the bulls was spread out over the course of the day with peaks in the afternoon and evening. Percentages of bulls feeding per pen never exceeded 20%, animals feeding mostly alone (during 28.04 ± 2.15% of total observation time) or in groups of two to three (16.61 ± 2.00% and 6.74 ± 1.90%). The order of bulls feeding after feed delivery varied indicating that all animals had similar access to fresh feed. These results emphasize the importance of constant feed availability and quality at any time of the day, thus indicating the ability of an AFS with six daily feedings to ensure such a consistency.